Effectiveness of Computer-Aided Instruction on Students’ Conceptual Understanding in Life Science - Mahawan, Alvin M.; Celedonio, Milagros A. (Future Science / FSH-PH Publications, 2023)
The study aimed to determine the effectiveness of computer-aided instruction (CAI) on students’ conceptual understanding in Life Science. The objectives of the study is to develop lesson plans with computer-aided instruction packages; assess the developed lesson plans in terms of congruency of objectives, learning experiences, assessment of learning outcomes, features of computer-aided instruction packages, and to determine the effect of CAI on students’ conceptual understanding. The study utilized the pre-experimental method. The study involved 27 students who took a Bioenergetics Achievement Test (B.A.T) before and after CAI. It was found out that developed daily lesson plans are excellent; congruency of lesson objectives (WM = 4.80), learning experiences (WM =4.76), assessment of learning outcomes (WM =4.79), and features of computer-aided instruction (WM =4.39). The test of the difference between the pre-test and post-test scores showed a significant result (t26=-14.30, p<0.01), and it was supported with the positive increase on the Learning Gain Score (LGS=3.18) which showed an increase in conceptual understanding and mastery in the learning competencies. Hence, there is sufficient evidence to show that the students’ scores improved significantly after being taught in computer-aided instruction. Therefore, the developed lesson plans with the integration of computer-aided instruction are excellently and effectively improved the students' conceptual understanding and mastery of the learning competencies.